No best world: creaturely freedom - Leftow, B (Cambridge University Press, 2005)
William Rowe and others argue that if this is a possible world than which there is a better, it follows that God does not exist. I now reject the key premise of Rowe's argument. I do so first within a Molinist framework. I then show that this framework is dispensable: really all one needs to block the better-world argument is the assumption that creatures have libertarian free will. I also foreclose what might seem a promising way around the 'moral-luck' counter I develop, and contend that it is in a way impossible to get around.